All‐Polymer Photonic Microcavities Doped with Perylene Bisimide J‐Aggregates. Issue 21 (25th August 2017) - Lova, Paola; Grande, Vincenzo; Manfredi, Giovanni; Patrini, Maddalena; Herbst, Stefanie; Würthner, Frank; Comoretto, Davide
Abstract: Thanks to exciting chemical and optical features, perylene bisimide J‐aggregates are ideal candidates to be employed for high‐performance plastic photonic devices. However, they generally tend to form π–π stacked H‐aggregates that are unsuitable for implementation in polymer resonant cavities. In this work, the efficient compatibilization of a tailored perylene bisimide forming robust J‐aggregated supramolecular polymers into amorphous polypropylene is introduced. The new nanocomposite is then implemented into an all‐polymer planar microcavity, which provides strong and directional spectral redistribution of the J‐aggregate photoluminescence, due to a strong modification of the photonic states. A systematic analysis of the photoemitting processes, including photoluminescence decay and quantum yields, shows that the optical confinement in the polymeric microcavity does not introduce any additional nonradiative de‐excitation pathways to those already found in the J‐aggregate nanocomposite film and pave the way to PBI‐based high‐performance plastic photonic devices. Abstract : A perylene bisimide J‐aggregate has been dispersed into an amorphous polypropylene matrix polymer, and implemented into planar microcavities via a solution‐based process. The microcavity provides strong directional spectral redistribution of the J‐aggregate photoluminescence. The new method offers easily processable solid‐state supramolecular J‐aggregates suitable for plastic‐photonic devices.